2D, Metal‐Free Electrocatalysts for the Nitrogen Reduction Reaction. (16th December 2022) - Liu, Chuangwei; Tian, Ang; Li, Qinye; Wang, Tianyi; Qin, Gaowu; Li, Song; Sun, Chenghua
Abstract: Environmentally friendly ammonia production is important for addressing the carbon emissions and substantial energy consumption that are currently associated with the chemical industry. In recent decades, many achievements are made in this area; however, low production yield, poor selectivity, and unsatisfactory Faradaic efficiency hinder large‐scale applications. 2D, metal‐free electrocatalysts stand out from other candidates because of their physical, electronic, and chemical properties. In this study, recent developments of 2D‐based electrochemical materials for converting dinitrogen into ammonia in ambient conditions are systematically reviewed. First, recent unique progress and challenges on novel 2D electrocatalysts for the nitrogen reduction reaction are summarized. Then, various synthetic strategies for electrochemical materials and the influence of these methods have on the intrinsic material performance are highlighted. Last, by comparing current engineering strategies, electrochemical tests, and computational calculations, the opportunities, critical issues, and scientific challenges for 2D nanomaterials as stable, efficient catalysts, are analyzed. On the basis of this comparison, technology solutions are provided and rational principles for future studies are proposed. Abstract : 2D materials, metal‐free, are considered as potential promising catalysts for ammonia synthesis under ambient conditions. This review comprehensively summarizes the recent advanced process in nitrogen fixation on 2D materials from the theoretical and experimental aspects. Especially, the structure–activity correlations are built up from the computational mind, and new data‐driven method is provided to design new catalyst.